O ensino de música no Curso de Iniciação Artística da Escola de Música da UFRN: um estudo a partir das lembranças de professoras - Silva, Cleide Alves da (2011)
This dissertation deals with the teaching of music in Rio Grande do Norte‟s Federal University Music School Arts Introductory Course an extension university course, to teach children music. The research aims to uncover and understand how the teaching of music has been developed in the area researched, beginning the study from the memories of five teachers who worked on it. The theoretical background focuses on studies about memory (BOSI, 1994; HALBWACHS, 2006 and TEDESCO, 2004). The methodological construction is supported by the principles of qualitative research, having the oral history been adopted as method. The live musical experiences, experimentation and music creation have characterized the classroom teaching practices of five teachers surveyed, with direct reflex on classes conducted during the course. The course curriculum and organization in the period researched reflected the active teachers‟ thinking and diverse backgrounds. The study about the experiences lived by others through memories - in this case, oral testimonies reported by teachers about teaching music to children at elementary levels in a fresh past aims to contribute to an understanding by the future generations, of past musical educational practices as well as helping to rethink the course‟s senses and meanings studied in the contemporaneity.